Enhancing the competitiveness and sustainability of social enterprises in Hong Kong: A three-dimensional analysis - Sidney Leung; Phyllis Mo; Howard Ling; Yanto Chandra; So Sum Ho (China Journal of Accounting Research, 2019)
Running a social enterprise (SE) is more difficult than running a small or medium-sized enterprise because SEs have to achieve both economic sustainability as business enterprises and their social mission for the benefit of society. After a few years of operation, many SEs fail or struggle for survival. In this study, we examine some of the factors that affect an SE's profitability, financial management, and business planning and management. Based on in-depth interviews with 22 social enterprises in Hong Kong, we find that SEs with the dual investment objectives of social mission and financial return are more sustainable and competitive than SEs with social impact as their sole objective. Furthermore, SEs managed by non-owner managers have better financial planning and performance than those managed by owner managers. In addition, SEs with an oversight/advisory committee are more competitive and have better management practices than those without such a committee. Our findings have policy implications for government, SEs, funding bodies, and non-profit organizations to enhance and promote the development of the social enterprise sector.
Keywords: 650; Advisory committee; Corporate governance; Social enterprise performance; Social enterprises; Social mission; Sustainability